2018
DOI: 10.1007/s00044-018-2136-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular docking, ctDNA interaction, DFT calculation and evaluation of antiproliferative and anti-Toxoplasma gondii activities of 2,4-diaminotriazine-thiazole derivatives

Abstract: Synthesis, characterization, and investigation of antiproliferative activities against human cancer cell lines (MV4-11, MCF-7, and A549) and Toxoplasma gondii parasite of twelve novel 2,4-diaminotriazine-thiazoles are presented. The toxicity of the compounds was studied at three different cell types, normal mouse fibroblast (Balb/3T3), mouse fibroblast (L929), and human VERO cells. The structures of novel compounds were determined using 1H and 13C NMR, FAB(+)-MS, and elemental analyses. Among the derivatives, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Due to the nonlinear optical properties (NLO) of the thiazole system, it is used in optical devices such as photovoltaic detectors or light-emitting diodes [14]. However, its greatest advantage is that it exhibits a wide range of biological properties, such as antimicrobial [15][16][17][18], anticancer [19][20][21], anticonvulsant [22], antioxidant [23] and anti-SARS-CoV [24]. Numerous studies, including those carried out over the years by our group, show that thiazole derivatives have high antifungal activity [3,25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nonlinear optical properties (NLO) of the thiazole system, it is used in optical devices such as photovoltaic detectors or light-emitting diodes [14]. However, its greatest advantage is that it exhibits a wide range of biological properties, such as antimicrobial [15][16][17][18], anticancer [19][20][21], anticonvulsant [22], antioxidant [23] and anti-SARS-CoV [24]. Numerous studies, including those carried out over the years by our group, show that thiazole derivatives have high antifungal activity [3,25].…”
Section: Introductionmentioning
confidence: 99%
“…R = F, Br, Cl, CH3, CF3, OCH3, 2,4-diF, CN, N3, NO2 The same authors presented a synthesis, characterization and invest proliferative activities against human cancer cell lines and Toxoplasma go twelve novel 2,4-diaminotriazine-thiazoles (Figure 17). Similarly, as in the vious compounds, the new derivatives were characterized by a much low values 9-68 times lower) than sulfadiazine used as a reference drug [83]. The same authors presented a synthesis, characterization and investigation of antiproliferative activities against human cancer cell lines and Toxoplasma gondii parasite of twelve novel 2,4-diaminotriazine-thiazoles (Figure 17).…”
Section: Thiazole Derivativesmentioning
confidence: 78%
“…The last years of the research have confirmed that thiazole scaffold has diverse biological properties that can be used to treat many diseases, such as microbial infections (Bikobo et al 2017;Secci et al 2012;Łączkowski et al 2018a, 2018bZaki et al 2018;Ansari et al 2018), Parkinson's disease (Carradori et al 2018), cancer (de Santana et al 2018;Łączkowski et al 2014, 2016a, 2016bPiechowska et al 2019;Gomha et al 2018), epilepsy (Siddiqui and Ahsan 2010;Ahangar et al 2011;Łączkowski et al 2016a, 2016b, toxoplasmosis (Schultz et al 2014;Łączkowski et al 2018a, 2018b, and antioxidants (Geronikaki et al 2013;Djukic et al 2018). Considering the above-mentioned findings, we decided to design and synthesize the structure of hybrids incorporating both the thiazole ring and the cyclohexenyl moiety.…”
Section: Introductionmentioning
confidence: 98%